Skeletal muscle density is an independent predictor of diffuse large B‐cell lymphoma outcomes treated with rituximab‐based chemoimmunotherapy. Issue 2 (21st November 2016) - Chu, Michael P.; Lieffers, Jessica; Ghosh, Sunita; Belch, Andrew; Chua, Neil S.; Fontaine, Amelie; Sangha, Randeep; Turner, Robert A.; Baracos, Vickie E.; Sawyer, Michael B.
Abstract: Background: While much cancer research focuses on tumours and their microenvironment, malignancies cause widespread physiologic changes. Cancer and treatment‐related sarcopenia, measured with quantitative imaging or as a decrease in overall body mass, are indicative of poor prognosis in elderly diffuse large B‐cell lymphoma (DLBCL) patients, skeletal muscle radiodensity (SMD) may be a better prognostic marker. SMD, a measure of muscle radiation attenuation on CT imaging, is more prognostic than sarcopenia or International Prognostic Index (IPI) scores in follicular lymphoma and multiple solid organ malignancies. Low SMD appears to correlate with fat accumulation in muscle and is associated with inflammation. This study set out to examine SMD's prognostic ability in DLBCL. Methods: All DLBCL patients treated with rituximab‐containing therapy between 2004 and 2009 were compared to determine SMD's prognostic ability in this single centre, retrospective study. Pre‐treatment CT scans were used to measure SMD and muscle cross‐sectional area. Primary endpoints included progression free (PFS) and overall survival (OS) while objective response rates (ORR) were secondary. Results: Of 224 evaluable patients, 116 were identified as having low SMD. Low SMD predicted poorer 5 year PFS, 60 vs. 81% ( p = 0.001) and OS, 58 vs. 86% ( p < 0.0001). SMD's prognostic ability retained significance in multivariate analysis taking into consideration the Revised International Prognostic Index (R‐IPI) and sex. Although high SMD was not predictive of ORR (95.4 vs. 91.4%, p = 0.17), it was strongly associated with radiographic complete response (85 vs. 66%, p = 0.0007). Contrary to previous findings, sarcopenia did not predict for poorer OS but suggested improved OS in elderly DLBCL patients (HR 0.38, p = 0.01). Conclusions: SMD is a novel prognostic (and potentially treatment predictive) marker independent of R‐IPI in DLBCL. It presents an inexpensive yet complementary assessment to R‐IPI for prognosticating DLBCL outcomes.